Physical characteristics and match performances in women's international versus domestic-level footbali players: a 2-year, league-wide study - Scott, D.; Haigh, J.; Lovell, R. (Science and Medicine in Football, 2020)
Objective: This study examined the role of physical qualities and physical match performances in distinguishing between elite performance levels in women's footbali.